2018
DOI: 10.1039/c7sc03627b
|View full text |Cite
|
Sign up to set email alerts
|

Photolabile coumarins with improved efficiency through azetidinyl substitution

Abstract: The efficiency of photoactivatable coumarins in water has been enhanced by substitution with azetidine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 33 publications
2
64
1
6
Order By: Relevance
“…The fluorescence quantum yield (F f )i saparticularly important factor for fluorescent probes because it often limits practical applications,s uch as environmental monitoring and biosensing events. [21] As observed from the results in Table 2, unlike 4,c hromophores 1-3 preserve lower F f values in CH 2 Cl 2 Figure 2. a) Fluorescence emission spectra of 5 in n-hexane/CH 2 Cl 2 of different ratios at ac oncentration of 10 mm;the excitationwavelengthisl = 400 nm.…”
Section: Resultssupporting
confidence: 59%
“…The fluorescence quantum yield (F f )i saparticularly important factor for fluorescent probes because it often limits practical applications,s uch as environmental monitoring and biosensing events. [21] As observed from the results in Table 2, unlike 4,c hromophores 1-3 preserve lower F f values in CH 2 Cl 2 Figure 2. a) Fluorescence emission spectra of 5 in n-hexane/CH 2 Cl 2 of different ratios at ac oncentration of 10 mm;the excitationwavelengthisl = 400 nm.…”
Section: Resultssupporting
confidence: 59%
“…The four new coumarin derivatives were isolated after silica column chromatography as purple (4Az-6Az) and dark blue (7Az) solids, and their purity was assessed by HPLC ( Figure S3). Characterization was carried out HR ESI-MS and 1D ( 1 H, 13 C, and 19 F) and 2D NMR.…”
Section: Design Synthesis and Characterization Of 7-azetidinyl-coumamentioning
confidence: 99%
“…As previously stated, the stabilization of the TICT excited state is a major cause for fluorescence quenching in polar solvents for many conventional fluorophores, although HBIND has been recently postulated as a deactivation mechanism of the excited state of coumarin 1. 13 Replacement of the 7-N,N-dialkylamino group in conventional coumarins with azetidine lead to a clear improvement in the fluorescent quantum yield of the fluorophore. (e.g.,  F = 0.06 for 1 and  F = 0.92 for 1Az in H 2 O).…”
Section: Photophysical Characterization Of 7-azetidinyl-coupy Fluoropmentioning
confidence: 99%
“…7a). Next, several MOF-based catalysts were explored for this reaction, including VNU-20, Fe 3 O(BDC) 3 2 (DABCO) as catalysts led to higher initial rates. However, 81% and 82% yields were obtained for the reaction aer 6 h. The transformation using the VNU-20 catalyst proceeded with lower initial rate in the rst 4 h reaction time.…”
Section: Catalytic Studiesmentioning
confidence: 99%
“…11 Wang et al synthesized a variety of C-3 functionalized coumarins via the Cu(OAc) 2 catalyzed reaction with cyclic ethers and cycloalkanes. 12 Cao et al developed a novel approach for the direct Csp 2 -H radical triuoromethylation of coumarins in the presence of Mn(OAc) 3 . 13 Zhou et al reported the cross-dehydrogenative coupling of coumarins with benzylic Csp 3 -H bonds utilizing Cu(OAc) 2 catalyst.…”
Section: Introductionmentioning
confidence: 99%